KEY DIRECTIONS AND WAYS OF IMPLEMENTING THE ONE BELT - ONE ROAD PROJECT - Tashmukhamedova Kamilla (Scholars Digest Publishing, 2023)
The article analyzes the One Belt One Road project and the transport and transit potential of Central Asia in the context of China's global transport policy, as well as key areas, mechanisms, tools and experience in implementing China's One Belt One Road foreign policy initiative.
Keywords: One Belt, One Road, global transport routes, transport corridor, strategic interests, socio-economic development.